Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/ijn.12192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of falls by inpatients in an acute care hospital in Korea using the Morse Fall Scale

Abstract: The purpose of this study was to determine the cut-off values of the Korean version of the Morse Fall Scale (MFS-K) that would be most useful in identifying hospitalized patients at risk of falls in an acute-care setting in Korea. This study was conducted using the medical records of 66 patients who fell and 100 patients who did not fall (no-fall patients) sampled from inpatients hospitalized at a tertiary acute-care hospital in Seoul during the period from 1 January to 30 November 2009. The optimal cut-off po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(40 reference statements)
0
10
0
5
Order By: Relevance
“…The results showed: about 52% of older adults hospitalized who were part of this study had high risk for falls according to the Morse scale score. In South Korea, 50% of patients had high risk of falls (30) . In a study conducted with patients from 18 to 88 years old in a hospital in Spain, it was assessed the risk of falls and then the falls that occurred throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed: about 52% of older adults hospitalized who were part of this study had high risk for falls according to the Morse scale score. In South Korea, 50% of patients had high risk of falls (30) . In a study conducted with patients from 18 to 88 years old in a hospital in Spain, it was assessed the risk of falls and then the falls that occurred throughout hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…These retrieved studies (Table 2) were analyzed and data on their validity were identified ( Table 1). The most common fall risk assessment tool was the Morse Fall Scale (MFS) tested in 8 studies, including one in which the scale was adapted for use in the South Korean healthcare system (Sung et al, 2014), followed by the Hendrich II Fall Risk Model (5 studies). Four studies validated the St Thomas's Risk Assessment Tool in Falling Elderly Inpatients (STRATIFY); in one, the scale was modified as The Northern Hospital Modified St Thomas's Risk Assessment Tool (TNH-STRATIFY).…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity and specificity have an inverse relationship: i.e., high sensitivity may be achieved at the expense of low specificity, and vice versa; however, a clinically useful predictive score should combine at least 70% sensitivity, and 70% specificity (Baek et al, 2014;Healey, Haines, 2013). Studies with a testing cut-off of 21 (Baek et al, 2014), 40 (Kim et al, 2007;Sung et al, 2014;Sung-Hee Yoo et al, 2015), 45 (Sung et al, 2014), 51 (Chapman et al, 2011;Kim et al, 2011;Baek et al, 2014), and 55 (Schwendimann et al, 2006) come closest to these values. Watson et al (2016) point to the predictive ability of the MFS to distinguish between high and low fall risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysed studies (Table 1) the authors validated various cut-off score values, frequently using the values of 40 (Kim et al, 2007), 45 (Chow et al, 2007;Sung et al, 2014), 51 (Beak et al, 2013 and 55 (Watson et al, 2016). The cut-off is understood as an acceptable score value to differentiate the normal from the abnormal (Polit, Beck, 2010), and helps to predict the fall risk for each patient; i.e., it distinguishes between low fall risk patients, and high fall risk patients, for whom preventative strategies should be implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation